Disentangling the effects of word frequency and contextual diversity on serial recall performance - Parmentier, Fabrice B. R (2017)
Research shows that contextual diversity (CD; the number of different contexts in which a word appears within a corpus) constitutes a better predictor of reading performance than word frequency (WF), that it mediates the access to lexical representations, and that controlling for contextual CD abolishes the effect of WF in lexical decision tasks. Despite the theoretical relevance of these findings for the study of serial memory, it is not known how CD might affect serial recall performance. We report the first independent manipulation of CD and WF in a serial recall task. Experiment 1 revealed better performance for low CD and for high WF words independently. Both effects affected omissions and item errors, but contrary to past research, word frequency also affected order errors. These results were confirmed in two more experiments comparing pure and alternating lists of low and high CD (Experiment 2) or WF (Experiment 3). The effect of CD was immune to this manipulation, while that of WF was abolished in alternating lists. Altogether the findings suggest a more difficult episodic retrieval of item information for words of high CD, and a role for both item and order information in the WF effect.